2008
DOI: 10.1213/ane.0b013e318168514b
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro, Inhibition of Mitogen-Activated Protein Kinase Pathways Protects Against Bupivacaine- and Ropivacaine-Induced Neurotoxicity

Abstract: Given equipotent doses, the neurotoxic potential of lidocaine does not appear to be significantly different from that of bupivacaine and ropivacaine in vitro. Moreover, bupivacaine and ropivacaine do not exert their neurotoxicity differently on specific subsets of dorsal root ganglion neurons. Their neurotoxic effects are brought about through the activation of specific MAPKs; the specific pharmacologic inhibition of these kinases attenuates toxicity in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 33 publications
2
71
0
Order By: Relevance
“…On the other hand, it has been shown that bupivacaine, at high concentration range (1-10 mM), can cause neurotoxicity. 43,44) In a clinical setting, bupivacaine is wellknown to produce central nervous system (CNS) toxicity in patients who exceed the recommended dosage (2 mg/kg). 45,46) The dose of bupivacaine used to inhibit KA-induced seizures in our study, therefore, may be considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that bupivacaine, at high concentration range (1-10 mM), can cause neurotoxicity. 43,44) In a clinical setting, bupivacaine is wellknown to produce central nervous system (CNS) toxicity in patients who exceed the recommended dosage (2 mg/kg). 45,46) The dose of bupivacaine used to inhibit KA-induced seizures in our study, therefore, may be considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…Medium was changed and cells were photographed daily with an inverted microscope (Carl Zeiss, Gottingen, Germany). We chose 24 and 48 h time points based on previous in vitro studies of LAs [10,13,19] . After image acquisition, the cells were trypsinized and stained with trypan blue (Mediatech).…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 99%
“…However, we cannot completely rule out that other signaling pathway(s) may also contribute to the LAinduced myotoxicity. It has been shown that both p38 MAPK and c-Jun N-terminal kinase (JNK) pathways are involved in bupivacaine-induced neurotoxicity [13] . In rat hippocampal slices, application of millimolar concentrations of lidocaine, but not bupivacaine, resulted in elevated expression of cleaved caspase 3, the primary executioner of apoptosis [38] .…”
Section: Wwwnaturecom/aps Maurice Jm Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has suggested that local anesthetics could induce apoptosis in human thyroid cancer cells, which is associated with mitogen-activated protein kinase (MAPK) pathways (13). Another report has suggested that inhibition of MAPK pathways protects against local anesthetics-induced neurotoxicity (14). However, little…”
Section: Introductionmentioning
confidence: 99%